CoCStom trial: study protocol for a randomised trial comparing completeness of adjuvant chemotherapy after early versus late diverting stoma closure in low anterior resection for rectal cancer - Şandra-Petrescu, Flavius Ionuţ; Herrle, Florian; Rossion, Inga; Post, Stefan; Hofheinz, Ralf-Dieter; Kienle, Peter (BMC cancer, 2015)
Current evidence supports a diverting stoma in patients undergoing low anterior resection with total mesorectal excision for rectal cancer as it reduces clinical severity of anastomotic leakage. However, relevant stoma morbidity after rectal cancer surgery exists and has a significant impact on quality of life. Moreover, a diverting stoma has an influence on completeness of chemotherapy but it remains unclear in which way. There is no evidence regarding optimal timing for stoma closure in relation to adjuvant chemotherapy. Two randomised controlled trials have studied early stoma closure after low anterior resection in patients with rectal cancer, one of them showing that early closure around day 8 after resection is possible without increasing morbidity.